Better Adaptive Text Compression Scheme - Duha Amir Sultan (مجلة التربية والعلم, 2018)
A data compression scheme suggested by Ziv and Lempel, LZ77, is applied to text compression. A slightly modified version suggested by Storer and Szymanski ,LZSS, is found to achieve compression ratios as good as most existing schemes for a wide range of texts. In these two methods and all other dynamic methods, a text file is searched from left to right to find the longest match between the lookahead buffer (the previously encoded text) and the characters to be encoded. The method suggested in this work depends the searching in two directions, from left to right and from right to left, although this process takes more time, better compression results were obtained